ANALISA PEMELIHARAAN ALAT SHORTWAVE DIATHERMY DI RUMAH SAKIT UMUM HERMINA MEDAN - Afrin Nazar; Siti Rahmah (Prodi Teknik Elektromedik Universitas Sari Mutiara Indonesia, 2018)
Shortwave Diathermy is one of the medical equipment that is a supporting aspect of the implementation of health service activities, and also really needs maintenance and supervision to avoid malfunctions. Shortwave Diathermy (SWD) is one of the therapeutic equipment and also a modality of heat with therapeutic application techniques using high-frequency radio electric currents by converting electromagnetic energy into heat energy. The purpose of this study was to determine the implementation of shortwave diathermy maintenance at Hermina General Hospital Medan. This research was conducted at General Hospital Hermina Medan Jl. Dormitory/Ampera II, Kec. Sei Sikambing C-II, Kec. Medan Helvetia by providing a questionnaire sheet containing questions/statements. The type of research used is a qualitative descriptive method conducted from June 2018. The results obtained from the respondents, from 24 questionnaires there were 23 questionnaires answered Yes and 1 questionnaire answered No. It was concluded that the implementation of the Shortwave Diathermy maintenance at Hermina General Hospital Medan was running properly, and was declared good.